Periodontal ligament proliferation and expressions of bone biomolecules upon orthodontic preloading: Clinical implications for tooth autotransplantation - Sasathorn Phutinart (2020)
© 2020 The Korean Association of Orthodontists. Objective: Preservation of the periodontal ligament (PDL) is vital to the success of tooth autotransplantation (TAT). Increased PDL volumes and facilitated tooth extraction have been observed upon orthodontic preloading. However, it is unclear whether any changes occur in the expressions of bone biomolecules in the increased PDL volumes. This study aimed to determine the expressions of runt-related transcription factor 2 (RUNX2), alkaline phosphatase (ALP), receptor activator of nuclear factor kappa-B ligand (RANKL), and osteoprotegerin (OPG) in PDL upon preloading. Methods: Seventy-two premolars from 18 patients were randomly assigned to experimental groups that received a leveling force for 1, 2, or 4 weeks or to a control unloaded group. Following extraction, PDL volumes from 32 premolars of eight patients (21.0 ± 3.8 years) were evaluated using toluidine blue staining. The expressions of the biomolecules in the PDL from 40 premolars of ten patients (21.4 ± 4.0 years) were analyzed via immunoblotting. Results: The median percentage of stained PDL was significantly higher at 2 and 4 weeks after preloading than in the unloaded condition (p < 0.05). The median RUNX2 and ALP expression levels were significantly higher at 2 and 4 weeks after preloading than in the unloaded condition (p < 0.05), whereas the median RANKL/OPG ratios were significantly higher at 1 and 4 weeks after preloading (p < 0.05). Conclusions: Orthodontic preloading for 4 weeks enhances PDL volumes as well as the expressions of RUNX2, ALP and the RANKL/OPG ratio in the PDL, suggesting this loading period is suitable for successful TAT.